Genomic analysis revealed a convergent evolution of LINE-1 in coat color: A case study in water buffaloes (Bubalus bubalis) - Liang, D.; Zhao, P.; Si, J.; Fang, L.; Pairo-Castineira, E.; Hu, X.; Xu, Q.; Hou, Y.; Gong, Y.; Liang, Z.; Tian, B.; Mao, H.; et al. (Oxford University Press, 2021)
Visible pigmentation phenotypes can be used to explore the regulation of gene expression and the evolution of coat color patterns in animals. Here, we performed whole-genome and RNA sequencing and applied genome-wide association study, comparative population genomics and biological experiments to show that the 2,809-bp-long LINE-1 insertion in the ASIP (agouti signaling protein) gene is the causative mutation for the white coat phenotype in swamp buffalo (Bubalus bubalis). This LINE-1 insertion (3′ truncated and containing only 5′ UTR) functions as a strong proximal promoter that leads to a 10-fold increase in the transcription of ASIP in white buffalo skin. The 165 bp of 5′ UTR transcribed from the LINE-1 is spliced into the first coding exon of ASIP, resulting in a chimeric transcript. The increased expression of ASIP prevents melanocyte maturation, leading to the absence of pigment in white buffalo skin and hairs. Phylogenetic analyses indicate that the white buffalo-specific ASIP allele originated from a recent genetic transposition event in swamp buffalo. Interestingly, as a similar LINE-1 insertion has been identified in the cattle ASIP gene, we discuss the convergent mechanism of coat color evolution in the Bovini tribe.